PENGARUH LINGKUNGAN EKONOMI, ORGANISASI, DAN ORIENTASI PASAR TERHADAP KINERJA PETANI KOPI - Bagus Qomaruzzaman Ratu Edi (RELASI : JURNAL EKONOMI, 2015)
BagusQomaruzzaman RatuEdi, 041520201002, Departement of Agribusiness, Postgraduate Program, University of Jember, research title: "The Effect ofEnvironmental Economics, Organization and PerformanceOrientationAgainstCoffee FarmersMarkets", under supervision guidance ofProf. Dr. KabulSantoso, MS, as supervisor andIr. RudiHartadi, MP, as co-supervisor. The purposeof this study wasto determine (a) Effect ofpartiallybetweentheeconomicperformance ofthe coffeegrowers(b) Effect ofpartiallybetweenfarmers' organizationswiththe performance ofthe coffeegrowers(c) Effect ofpartialperformancebetween market orientationwithcoffee farmers(d) Effect ofeconomic environment, organizations of farmersand market orientationon performancesimultaneouslycoffee farmers. The methodof researchuseddescriptivemethodcorelasional, the study areais determinedbythe sampling methodintentionally (purposive sampling method) andsamplingdoneintentionally(purposive). Conclusion Thestudy showed(1)There isa partialeffect oftheeconomic environmenttheperformance ofcoffee farmers, (2)There isa partialinfluencebetween the organizationof coffeefarmerswith theperformance of thefarmers, (3) Nopartialeffectbetween market orientationwith theperformance of thecoffee growers, (4)There is asimultaneouseffect ofthe economic environmentand farmers' organizationsto Performancefarmer.